Vulnerability and Reproductive Choices of Households in Benin - TOKPEICHAN, Adéoti Nicolas; LANHA, MAGLOIRE BONAVENTURE JOSEPH (My University, 2025)
This paper aims to analyze the influence of fertility on household vulnerability in Benin. It proposes a theoretical framework that breaks down economic vulnerability into vulnerability due to household poverty and vulnerability due to general risks and idiosyncrasy. It then regresses each of the vulnerabilities on the observable characteristics of households. This application is made with data from the 2021/22 Harmonized Survey on Household Living Conditions (EHCVM) on Benin. The results show that the number of children has a positive effect on vulnerability, thus absorbing the positive effect on risk-related vulnerability. These results suggest that incentives for parental responsibility should be put in place and social protection systems should be strengthened for vulnerable low-fertility households.
Keywords: Household - Fertility - Children; Vulnerability